2016
DOI: 10.1002/cnm.2790
|View full text |Cite
|
Sign up to set email alerts
|

A finite element model to investigate the effect of ulnar variance on distal radioulnar joint mechanics

Abstract: Ulnocarpal impaction syndrome involves excessive loading of the ulnocarpal joint. Ulnar shortening osteotomies are an effective way to reduce ulnocarpal loading but alter contact mechanics at the distal radioulnar joint (DRUJ). This study used a computational model to investigate the relationship between ulnar length and DRUJ mechanics. Detailed, finite element models of the radius and ulna bones were constructed from magnetic resonance imaging data. The length of the ulna bone model was increased and decrease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 47 publications
1
10
0
Order By: Relevance
“…UV was shown to affect ulnocarpal loading in several cadaveric studies. These studies, in which load was transmitted through the TFCC, confirmed the influence of UV on ulnocarpal loading (15). There are several UV measurement techniques, such as perpendicularis, central reference point, and lateral view.…”
Section: Discussionmentioning
confidence: 57%
“…UV was shown to affect ulnocarpal loading in several cadaveric studies. These studies, in which load was transmitted through the TFCC, confirmed the influence of UV on ulnocarpal loading (15). There are several UV measurement techniques, such as perpendicularis, central reference point, and lateral view.…”
Section: Discussionmentioning
confidence: 57%
“…To the best of our knowledge, no other research article is available on whole-bone testing of the elbow. A few research groups, including Burkhart et al, 33 Johnson and Troy, 34 Sakai et al, 36 and Greybe et al 38 have used femur bone values for modeling and design of elbow-related mechanics. However, the bending strength of whole-bone femur samples for the same age group is 195 ± 3.9 MPa.…”
Section: Resultsmentioning
confidence: 99%
“…36 Sakai et al used an elastic modulus of 17 GPa from the experimental results of sectioned frozen femur cortical bones reported by Reilly et al 37 In a study carried out by Greybe et al, the authors developed an FE model to study the effect of ulnar shortening (a treatment for ulnocarpal impaction syndrome) on distal radioulnar joint mechanics. 38 Greybe et al used an elastic modulus of 18 GPa of sectioned frozen cortical bone samples of femur and tibia by Rho and colleagues. 39 There is no uniformity of reference values because of the unavailability of the data.…”
Section: Introductionmentioning
confidence: 99%
“…This method is widely used in mechanical engineering to quantify the biomechanical behaviors of complex structures under external forces. [7][8][9][10][11] A considerable amount of literatures have studied the forearm bone strength, microarchitecture, and the comparison between normal and osteoporotic bones in elderly people using FEM. Newitt et al 12 focused on finding the effect of the trabecular region properties of the radius on the force transmission through the distal radius that, in turn, would cause bone fracture in postmenopausal women with and without bone mineral density (BMD) disorders.…”
Section: Introductionmentioning
confidence: 99%